2011
DOI: 10.1161/atvbaha.111.225771
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the EMMPRIN (CD147)–Cyclophilin A Interaction Reduces Infarct Size and Preserves Systolic Function After Myocardial Ischemia and Reperfusion

Abstract: Introduction Inflammation and proteolysis crucially contribute to myocardial ischemia and reperfusion injury. The Extracellular Matrix Metalloproteinase Inducer (EMMPRIN, CD147) and its ligand Cyclophilin A (CyPA) may be involved in both processes. The aim of the study was to characterize the role of the CD147 and CyPA interplay in myocardial ischemia/reperfusion (I/R) injury. Methods and results Immunohistochemistry showed enhanced expression of CD147 and CyPA in myocardial sections from human autopsies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 49 publications
8
110
1
Order By: Relevance
“…Indeed, the inflammatory response in BA, both in the mouse model and in humans, is associated with infiltration by neutrophils, which form inflammatory foci around the areas of bile duct obstruction (21)(22)(23). Modulation of neutrophil infiltration by the inhibition of extracellular cyclophilins or their receptor CD147 has been reported in rheumatoid arthritis (38,39), lung inflammation (14) and myocardial ischemia and reperfusion injury (40). The decreased migration of neutrophils and other inflammatory cells to the liver may explain the decreased levels of IL-6 observed in MM284-treated animals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the inflammatory response in BA, both in the mouse model and in humans, is associated with infiltration by neutrophils, which form inflammatory foci around the areas of bile duct obstruction (21)(22)(23). Modulation of neutrophil infiltration by the inhibition of extracellular cyclophilins or their receptor CD147 has been reported in rheumatoid arthritis (38,39), lung inflammation (14) and myocardial ischemia and reperfusion injury (40). The decreased migration of neutrophils and other inflammatory cells to the liver may explain the decreased levels of IL-6 observed in MM284-treated animals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…28 Animal studies were approved by the local authorities (regional board Tübingen) and conducted according to German law for the welfare of animals.…”
Section: Micementioning
confidence: 99%
“…8,[28][29][30] Briefly, murine blood from the retroorbital plexus was collected and centrifuged at 640g for 5 minutes at room temperature. To obtain platelet-rich plasma, the supernatant was centrifuged at 260g for 6 minutes.…”
Section: Platelet Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many previous studies have demonstrated that CyPA knockdown serves to protect individuals from the detrimental effects of inflammation associated with many diseases, including atherosclerosis , ischemia/reperfusion injury (Seizer et al 2011), and tumor growth in vivo (Li et al 2008).…”
Section: Introductionmentioning
confidence: 99%